Water electrolysis steril
By employing a dimensionally stable proton exchange membrane with low noble metal loading, the catalyst coating film achieves high efficiency and power density in water electrolysis systems, addressing the challenges of cost and electrode integrity.
Patent Information
- Application Number
- JP2023522538
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-13
- Filing Date
- 2021-10-07
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-10-07
AI Technical Summary
Current water electrolysis systems require high noble metal loadings in catalysts to maintain efficiency, leading to increased costs and potential losses in electrode integrity due to membrane expansion under wet conditions.
A catalyst coating film with a low noble metal loading of 0.6 mg/cm², achieved through the use of dimensionally stable proton exchange membranes with less than 20% area expansion when exposed to heated water, ensuring high efficiency and integrity at low current densities.
The low noble metal loading catalyst coating film maintains high efficiency and power density while reducing costs, with improved dimensional stability preventing electrode integrity loss even at high current densities.
Smart Images

Figure 0007665020000001 
Figure 0007665020000002 
Figure 0007665020000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a catalyst coated membrane having high power density at low catalyst loading, and a water electrolysis cell comprising the catalyst coated membrane. [Background technology]
[0002] Catalyst coated membranes, which have a proton exchange membrane coated with an anode on one side and a cathode on the other side, are known from the prior art under the term CCM (catalyst coated membrane). When CCMs are used for water electrolysis, the term PEM-WE (proton exchange membrane water electrolysis) is customary.
[0003] Proton exchange membranes used in PEM-WE are typically extruded polymer membranes based on perfluorosulfonic acid (PFSA). The most established examples of PEMs are Chemours' Nafion™ N115 and Nafion™ N117. Thinner cast membranes, i.e. solvent printed membranes such as Nafion™ NR212, continue to be used in the current literature.
[0004] In the anode electrode layer (anode for short) a catalyst is used for the oxidation of water (water splitting). This catalyst is often called OER (Oxygen Evolution Reaction) catalyst. OER catalysts are usually based on precious metals and contain precious metal oxides that show high catalytic activity in water splitting. In addition, the anode usually uses a proton conducting polymer, the so-called PFSA type ionomer, as a binder that exists in a mixture with the OER catalyst.
[0005] In the cathode electrode layer (cathode for short) catalysts are used to reduce the protons to hydrogen (Hydrogen Evolution Reaction = HER catalysts). These catalysts are usually based on platinum, which is preferably present in finely dispersed form on a carbon powder. In addition, the cathode usually also contains a PFSA-based ionomer as a binder.
[0006] CCMs for PEM-WE applications are currently manufactured with high contents of the precious metals iridium and / or ruthenium, with typical areal weights, also referred to as (precious metal) loadings, of 1 to 2 mg / cm 2 which ensures a sufficient OER rate. The areal weight (mg) here refers to the mass of the catalytic metal, and the area (cm 2 ) refers to the geometric area of the CCM on which the catalyst resides. This area is also called the active area. Until now, such large areal weights were necessary to prevent a loss of efficiency. Studies (see for example M. Bernt et al., The Electrochemical Society, 165(5) F305-F314 (2018)) have shown that these losses can be as low as 0.4 mg / cm 2 The publications suggest addressing this problem by making thicker electrodes, but do not teach how to make the thicker electrodes without simultaneously increasing the iridium loading. Summary of the Invention [Problem to be solved by the invention]
[0007] It is therefore an object of the present invention to provide a catalyst coated membrane having good efficiency at low anode precious metal loadings, characterized by low voltage at a given current density, and similarly, to identify a water electrolysis cell having good efficiency and therefore also low operating costs as a result of reduced power consumption. [Means for solving the problem]
[0008] This object is achieved by the independent claims. The dependent claims describe advantageous developments and configurations of the invention.
[0009] Thus, according to the invention, a catalyst coated membrane is described, consisting of a proton exchange membrane (membrane for short), an anode applied to a first side of the membrane and a cathode applied to a second side of the membrane. The anode is characterized by a low catalyst loading and for this purpose consists of at least one precious metal-containing catalyst, the areal weight of the precious metal-containing catalyst being less than 0.6 mg / cm, based on the precious metal content in the precious metal-containing catalyst. 2 As explained below, this low loading of precious metal-containing catalyst in the catalyst coated membrane according to the present invention is sufficient to achieve low voltages and therefore high efficiencies at a given current density.
[0010] Such low loading is made possible by the areal expansion of the catalyst-coated membrane after 2 hours in water heated to 100° C. at an atmospheric pressure of 1013 hPa being less than 20%. This means that the catalyst-coated membrane according to the invention has high dimensional stability. The high dimensional stability of the catalyst-coated membrane described according to the invention is largely due to the high dimensional stability of the proton exchange membrane used, since the catalyst layer provided, when used as intended according to the invention, generally does not undergo high dimensional changes (even after 2 hours in water heated to 100° C. at an atmospheric pressure of 1013 hPa). In other words, this means that if the membrane used according to the invention has an areal expansion of less than 20% after 2 hours in water heated to 100° C. at an atmospheric pressure of 1013 hPa, the catalyst-coated membrane produced with this membrane will likewise have a corresponding areal expansion of less than 20% (after conditioning at 21° C. and 50% relative humidity, which corresponds to the reference values for the dimensions of the catalyst-coated membrane at ambient conditions). Considering that the overall dimensional stability of the catalyst coated membrane is key to the present invention, the area expansion refers according to the present invention to the area expansion of the catalyst coated membrane. The dimensional stability and therefore the area expansion of the catalyst coated membrane of the present invention will be explicitly explained in the experimental section below, where catalyst coated membrane is understood in the context of measuring the area expansion to mean a membrane coated with catalyst on one or both sides (depending on the manufacturing process).
[0011] By using a dimensionally stable membrane as defined above, 2For example, 0.2 mg / cm 2 , and even 0.1 mg / cm 2 Good efficiencies can be achieved at low anode loadings.
[0012] Without being bound by theory, it is hypothesized that the high efficiency of combining a dimensionally stable (catalyst-coated) membrane with an anode having a low precious metal loading is due to the fact that the dimensionally stable membrane ensures the integrity of the anode during installation of the catalyst-coated membrane in the cell and during operation under wet conditions. In contrast, when a membrane with low dimensional stability, i.e., an area expansion of more than 20%, is used according to the process described herein, the membrane expands excessively under wet operating conditions and the anode loses its integrity and the electrode resistance increases, which leads to a decrease in efficiency, especially at high current densities. This loss of electrode integrity is almost non-existent at high precious metal loadings, as adequate anode connectivity is maintained, but is only about 0.6 mg / cm. 2 Below this loading the losses will be too great to be acceptable.
[0013] On the other hand, in the dimensionally stable catalyst coated membrane according to the invention, the integrity of the anode is maintained even at very low precious metal loadings. This can be further demonstrated by the fact that at low current densities, where the efficiency is determined by the catalytic activity (and not the resistance), very similar cell voltage values are obtained for both membrane types (dimensionally stable and non-dimensionally stable) over the entire loading range. Moreover, the cell voltage trends are consistent with the theoretically expected cell voltage trends. Conversely, membranes with high dimensional stability, and therefore in the context of the present invention, catalyst coated membranes with high dimensional stability, are more stable at high current densities where the resistance becomes important, e.g. >1 A / cm. 2 Thus, lower anode precious metal loadings have clear advantages.
[0014] According to the present invention, the terms "loading", "precious metal loading" or "areal weight" refer exclusively to the precious metal present in the catalyst used. In the case of precious metals, the metals make up a particularly high proportion of the cost of the catalyst, so the use of a loading based on precious metals is advantageous.
[0015] Furthermore, the dimensional stability of the membrane used according to the invention, and thus of the catalyst-coated membrane according to the invention, is understood to mean the dimensional stability during the transition from the dry state to the wet state. Here, the expansion occurring in the membrane, and thus in the catalyst-coated membrane, describes the area expansion resulting from the expansion in two mutually perpendicular directions. By mutually perpendicular directions, it is understood here to mean the direction of expansion in the same plane, and not the expansion of the catalyst-coated membrane in the direction of the thickness or arrangement of the layers. More specifically, the mutually perpendicular directions are understood to mean the directions of expansion in the machine direction (MD) and the transverse direction (TD), also called the width direction, and the change in area can be expressed as a percentage area expansion. In the context of the present invention, high dimensional stability means a low area expansion, always less than 20%.
[0016] Now, for a membrane that has a dry length of 100 mm (MD) and a dry width of 100 mm (TD), which increases to a length of 115 mm (MD) and a width of 125 mm (TD) after immersion for 2 hours in water heated to 100°C at an atmospheric pressure of 1013 hPa, as will be explained in more detail below, the area expansion ratio is 43.75%.
[0017] A membrane having high dimensional stability, and thus a catalyst-coated membrane, in the context of the present invention, has an area expansion rate of less than 20% after being kept for 2 hours in water heated to 100° C. at an atmospheric pressure of 1013 hPa. The catalyst-coated membrane can be obtained by various methods, and there is no particular limitation on the manufacturing method.
[0018] According to a first exemplary process, one or more reinforcing structures are incorporated into the proton exchange membrane, so that the reinforcing structure(s) limit the expansion of the membrane. The reinforcing structure can be introduced, for example, during the process of producing the membrane from an ionomer dispersion or ionomer solution. In this case, a preformed reinforcing structure, such as (biaxially stretched) PTFE (ePTFE, expanded PTFE), is impregnated with the ionomer dispersion and dried so that the pores of the reinforcing structure are filled with the ionomer. Afterwards, a high temperature process, for example heating at about 150°C to 200°C, can be performed to improve the stability of the membrane.
[0019] The ionomer used is preferably a PFSA ionomer.
[0020] A reinforced membrane can also be obtained by laminating one or more non-reinforced membranes with a reinforcing structure, for example by pressing or calendering. A membrane with multiple reinforcing structures can be obtained, for example, by laminating (for example by pressing or calendering) two or more membranes, at least two of which have a reinforcing structure. This makes it possible to obtain a membrane with two or more reinforcing structures and very high dimensional stability, i.e., the area expansion is less than 10% when the membrane is kept in water heated to 100° C. at an atmospheric pressure of 1013 hPa for 2 hours.
[0021] Suitable reinforcing structures are, for example, woven or nonwoven polymer structures, porous ceramic thin films, perforated polymeric or inorganic membranes, or biaxially stretched porous polymeric membranes. Preferred reinforcing structures are also porous thin films of expanded polytetrafluoroethylene (ePTFE) or polyolefins, which allow the production of thin, but strong, membranes with excellent electrochemical performance.
[0022] According to a second exemplary process, a dimensionally stable membrane can be obtained by increasing the equivalent weight (EW) of the ionomer, thereby limiting the absorption of water by the membrane. EW here refers to the mass of polymer per mole of ionic functional groups present in the ionomer. Depending on the type of ionomer used, a person skilled in the art can determine the appropriate minimum equivalent weight that does not exceed the desired areal expansion, e.g., less than 20%. Unreinforced membranes made of ionomers with such equivalent weights can be produced, for example, by extrusion or solvent-based coating processes.
[0023] The above steps, i.e. the introduction of one or more reinforcing structures and the increase in equivalent weight, can furthermore be combined.
[0024] Since it is possible to obtain thin membranes, for example with layer thicknesses in the region of 50 μm, which have very good dimensional stability, good mechanical properties and low ionic resistance, which is particularly advantageous for the use of the invention in water electrolysis cells, preference may in principle be given to the step of introducing one or more reinforcing structures into the membrane.
[0025] The ionomers used in the polymer electrolyte membranes and catalyst layers used in accordance with the present invention are not particularly limited and may be perfluorinated ionomers (PFSA), partially fluorinated or hydrocarbon-based (non-fluorinated) ionomers, and it is possible to use different ionomers in different layers of the catalyst coated membrane.
[0026] The membrane may also be composed of sublayers that can contain different ionomers. Examples of PFSA type ionomers include Nafion™ from Chemours, Aquivion™ from Solvay Specialty Polymers, 3M ionomers, Aciplex™ from Asahi Kasei or Flemion™ from Asahi Glass. Examples of hydrocarbon-based ionomers include sulfonated polyetherketone (sPEK), sulfonated polyetheretherketone (sPEEK), sulfonated polyketoneketone (sPKK), sulfonated polysulfone (sPSU), sulfonated polyethersulfone (sPES), etc.
[0027] According to an advantageous development, the area expansion of the catalyst coated membrane as described herein after 2 hours in water heated to 100° C. at an atmospheric pressure of 1013 hPa is less than 15%, in particular less than 10%, which makes it possible to increase the efficiency of the catalyst coated membrane and achieve particularly low voltages for a given current density.
[0028] To further reduce the cost of the catalyst coated membrane while maintaining high efficiency, the areal weight based on the precious metal content of the precious metal-containing catalyst is preferably less than 0.4 mg / cm 2 Below, especially 0.35 mg / cm 2 The following applies.
[0029] The areal weight of the precious metal-containing catalyst based on the precious metal content is preferably 0.02 mg / cm 2 Above 0.05 mg / cm 2 This would be advantageous in the context of optimizing the catalytic performance of the catalyst coated membrane while minimizing financial expenditure.
[0030] For very good OER activity, the precious metal of the at least one precious metal-containing catalyst is selected in particular from iridium and ruthenium, which means that both iridium and ruthenium may be used individually or in combination as the precious metal-containing catalyst.
[0031] It is particularly advantageous in the context of high catalytic stability alongside excellent OER activity when the precious metal-containing catalyst is selected from iridium oxide, ruthenium oxide, mixtures thereof, and alloys thereof. Other elements can also be added to improve the activity and / or stability of the OER catalyst. Any alloying metal may be selected from, in particular, tin (Sn), niobium (Nb), nickel (Ni), tantalum (Ta), titanium (Ti), cobalt (Co), zinc (Zn), platinum (Pt), iron (Fe), silicon (Si), and cerium (Ce), with the alloying metal being present in the alloy at a content of less than 50% by weight.
[0032] Iridium and ruthenium oxides can be present, for example, in the form of nanoparticles or as a thin film coated on a substrate. In the case of nanoparticles, the catalyst oxides can be free-standing, agglomerated or finely dispersed on the substrate, typically being powders with a high specific surface area, such as titanium oxide. When the catalyst is present in the form of a thin film, it is possible to use either inorganic substances, such as ceramics, or organic compounds, such as polycyclic molecules, such as perylene, as the substrate.
[0033] OER catalytic oxides can be obtained by wet-chemical methods, for example by precipitation of hydroxides starting from soluble salts followed by heat treatment in air, or by thermal, dry processes (e.g. "Adam's fusion method"), or by gas-phase processes. Various methods for the synthesis of iridium oxides are summarized by way of example in J. Hansaem and L. Jaeyoung (Energy Chemistry, Vol. 46, July 2020, pp. 152-172).
[0034] To further improve the efficiency of the precious metal-containing catalyst at low loadings together with high anode conductivity, the precious metal-containing catalyst is preferably supported on an inorganic and / or ceramic support, in particular titanium oxide and / or niobium oxide and / or antimony-doped niobium oxide and / or tin oxide and / or antimony-doped tin oxide.
[0035] According to a further advantageous development, the cathode comprises a platinum-containing and / or palladium-containing cathode catalyst, which is in particular present on a carbon-containing support material. This is advantageous, since the platinum-containing and / or palladium-containing cathode catalyst has a particularly high HER activity and contributes to the power density of the catalyst-coated membrane according to the invention. It is also noted here that the dimensional stability of the catalyst-coated membrane is essentially unaffected by the provision of the cathode, so that in the case of a catalyst-coated membrane having an anode and a cathode, the areal expansion of the catalyst-coated membrane after 2 hours in water heated to 100° C. at an atmospheric pressure of 1013 hPa is less than 20%.
[0036] It is further advantageous if the proton exchange membrane has a layer thickness of 5 to 120 μm, more particularly 15 to 90 μm, more particularly 35 to 75 μm, whereby an optimal balance between efficiency and dimensional stability is achieved.
[0037] It is possible to use thicker membranes, for example up to 200 μm, but the high proton resistance of the membranes leads to a significant decrease in efficiency, especially at high current densities. When using membranes in the lower thickness range, i.e., about 50 μm or less, it is preferable to include a hydrocarbon-based ionomer in at least the lower layer of the membrane to reduce gas permeability from one side of the catalyst-coated membrane to the other side of the catalyst-coated membrane. Hydrocarbon-based ionomers have inherently lower gas permeability than PFSA ionomers. Crossover, especially of hydrogen, must be minimized to prevent the formation of explosive mixtures on the anode side and a decrease in current efficiency. Furthermore, in the low thickness region, the use of reinforced membranes is desirable to improve mechanical properties and long-term stability (thousands of hours of operation).
[0038] It is further advantageous if the proton exchange membrane contains at least one recombination catalyst, in particular platinum particles, which are preferably finely dispersed within the membrane, which catalyzes the reaction of hydrogen crossing over from the cathode to the anode with oxygen from the anode side, so as to prevent the formation of an explosive mixture on the anode side of the cell.
[0039] The anode and cathode of the catalyst coated membrane of the present invention can be manufactured by conventional methods. This can be done, for example, by dispersing the ground precious metal-containing catalyst together with an ionomer binder in an organic solvent or in a mixture of water and one or more organic solvents. The dispersion is optionally agitated with a high-energy mixer to allow good dispersion and reduce the size of the catalyst aggregates. Using a coating or printing device, the ink or paste thus obtained is applied or printed directly onto the membrane surface (first or second side of the proton exchange membrane) or first onto an inert substrate, called a decal. The coating or printing device employed can be, for example, a doctor blade, a slit nozzle, a coating roller, or a screen printing or gravure printing process. The liquid medium is then evaporated to form a thin electrode layer. After application of one or both electrodes to the inert substrate, the dried electrodes are transferred to the membrane surface by heat and pressure.
[0040] In an alternative embodiment, it is also possible to coat or print the ink or paste for producing the cathode directly onto the porous transport layer, in particular the gas diffusion layer. In this case, the term gas diffusion electrode (GDE) is used. The anode is applied onto the membrane by a decal process or direct membrane coating, resulting in what is known as a single-sided catalyst-coated membrane or half-CCM. The catalyst-coated membrane (both sides) is then mounted in an electrolytic cell, and a connection between the cathode catalyst layer and the membrane is obtained under the operating conditions of the cell.
[0041] Also according to the present invention, a water electrolysis cell is described that includes a catalyst coated membrane as disclosed above. The use of the catalyst coated membrane of the present invention provides the water electrolysis cell according to the present invention with the distinctive features of high power density and high efficiency at relatively low manufacturing costs.
[0042] Working Example method Determination of dimensional stability (area expansion) of membranes / catalyst-coated membranes (abbreviated CCMs) upon water absorption The membrane or membrane coated with catalyst on one or both sides (semi-CCM or CCM) was conditioned at 21° C. and 50% relative humidity until the size / dimension did not change any more. Then, a square with a side length (L) of 80 mm×80 mm was cut, e.g., using a cutting mold (L dry The square pieces (membrane, half CCM or CCM) were then precisely cut using a caliper (=80 mm). The two edges were aligned along the machine direction and cross machine direction, respectively. The orientation was marked with a permanent marker. The square pieces (membrane, half CCM or CCM) were then kept in water heated to 100°C at an atmospheric pressure of 1013 hPa for 2 hours, removed from the water and quickly wiped off excess water drops, and the edge length of the square was measured with a vernier caliper to a resolution of 0.01 mm. The edge length L 1,wet and L 2,wet It was decided.
[0043] The percent change in area was calculated according to the following formula: 100×[(L 1,wet ×L 2,wet )-L dry 2 ] / L dry2
[0044] Measuring the swelling behavior and therefore the areal expansion of the membrane, half CCM or CCM at 100°C (which corresponds to the temperature of water heated to 100°C at an air pressure of 1013 hPa) is a condition established in the prior art and also correlates with the swelling behavior of the membrane in water and therefore the swelling behavior of the half CCM or CCM under other conditions, for example at room temperature, especially in hot water (which are the usual operating conditions of the membrane, half CCM or CCM). In other words, membranes / semi-CCMs / CCMs that show a greater swelling behavior at 100°C and therefore have a high areal expansion also show a greater swelling behavior at lower temperatures. However, measuring the swelling behavior at 100°C offers the advantage that this temperature is closely controlled by the boiling point of water and is therefore applied according to the present invention.
[0045] Power / Efficiency in Water Electrolysis Cells The efficiency of CCM is 25 cm 2 The measurements were performed in a single cell with an active area of 1000 nm. The cell consisted of platinized titanium plates with a column bar flow field design on the anode and cathode sides. The flow field plate on the cathode side was additionally gold plated. Titanium sintered compacts (1 mm thick) and carbon paper (Toray TGP-H-120) were used for the porous transport layers and gas diffusion layers on the anode and cathode sides. The cell was closed with six M8 screws with a torque of 10 Nm. Deionized water with a conductivity of 1 μS / cm or less was circulated on the anode side. The cell was heated from room temperature to 60 °C over 20 min through a heating pad placed on the end plate. It was then heated to 80 °C over 20 min. The current was measured from 0 to 1 A / cm. 2 The cell was conditioned by cycling between 1 A / cm for 10 cycles with a 5 min hold time at each step. At the end of conditioning, the cell was cycled at 1 A / cm 2 The temperature was kept at 40° C. for 10 minutes.
[0046] The current-voltage characteristics (polarization curves) were measured at 80°C and 65°C by changing the current density from low to high (A / cm 2) with a holding time of 10 minutes each time. The steps were as follows: 0.01 0.02 0.03 0.05 0.08 0.1 0.2 0.4 0.6 0.8 1.0 1.2 1.4 1.6 1.8 2.0 2.25 2.5 2.75 3.0 (all in A / cm 2 unit)
[0047] Anode ink production 20.00 g of a commercial iridium-based catalyst (Elyst Ir75 0480, Umicore, Germany, IrO2 supported on TiO2; 75 wt.% iridium) was mixed with 10.20 g of Nafion™ D2020 ionomer dispersion (Chemours, USA) with 20.2 wt.% ionomer content. Then, 0.5 g of water and 69.30 g of 2-propanol were added. The mixture was dispersed for 30 min by a bead mill using spherical zirconia beads with a diameter of 1 mm. The stirring disc had a diameter of 45 mm and a rotation speed of 2130 rpm. The quality of the dispersion was ensured by visual inspection for the absence of catalyst agglomerates. The quality of the dispersion was further confirmed by good coating quality, i.e., no visible agglomerates or streaking in the wet or dry layers.
[0048] Fabrication of anodes with varying iridium loading on the decal The anodic ink was applied to a glass fiber reinforced PTFE substrate, i.e., a decal, using a spiral applicator (wire bar). The wet film thickness was gradually increased by selecting different spiral applicators with increasing wire thicknesses, resulting in an iridium metal loading (face weight) of 0.15 mg / cm. 2 , 0.25 mg / cm 2 , 0.5 mg / cm 2 , 1.0 mg / cm 2 , and 2.25 mg / cm 2The thickness of the wet layer was varied here between 10 μm and 285 μm by selecting a spiral applicator with an appropriate wire diameter. After coating, the wet layer was dried in an oven at 110° C. for 5 minutes. The actual iridium metal loading was determined gravimetrically by recording the exact decal weight before and after CCM lamination, as described in Example 1.
[0049] Example 1: Fabrication of catalyst coated membranes (CCMs) with high dimensional stability (low areal expansion) and varying anode catalyst loadings A membrane with high dimensional stability and a thickness of 41 μm was obtained, containing two expanded PTFE (ePTFE) reinforcement structures, by laminating a 25 μm thick unreinforced PFSA membrane between two 8 μm thick reinforced PFSA membranes. The membrane was laminated for 1 min in a press at a temperature of 160 °C and a pressure of 1.5 MPa. The machine directions of the three membranes were in each case arranged parallel to each other. The linear expansion of the membranes due to water absorption (at 100 °C) was measured, giving values of 2.0% and 3.3%. The resulting area expansion was 5.4%.
[0050] Using this type of membrane, five CCMs were fabricated using a press by decal process, in which the membrane was placed between anode and cathode decals (5 cm × 5 cm) and pressed at a temperature of 180 °C and a pressure of 1.5 MPa for 1 min, thereby transferring the electrode layer from the decal substrate to the membrane.
[0051] The cathode was the same for all CCMs and consisted of a catalyst of platinum on a carbon support and a Nafion™ ionomer binder. The weight ratio of catalyst to ionomer in the cathode was 3:1, and the platinum loading was 0.3 mg / cm. 2 This cathode was also applied to glass-fiber reinforced PTFE.
[0052] In the preparation of the CCMs, the anode loading of the different CCMs was, however, varied by using anode decals with varying loadings as described in the section "Preparation of anodes with varying iridium loadings on the decal". The actual anode loading was determined gravimetrically by measuring the weight of the anode decal before transfer (anode electrode on PTFE substrate) and after transfer (pure PTFE substrate). The areal weight (loading) of iridium was calculated by determining the difference (anode decal minus pure PTFE substrate) and including the known composition of the dry electrode layer. For the five CCMs, the following anode iridium loadings were obtained: 0.162 mg / cm 2 , 0.261 mg / cm 2 , 0.474 mg / cm 2 , 1.029 mg / cm 2 , and 2.072 mg / cm 2 It is.
[0053] In addition, 0.261 mg / cm 2 A CCM with an anodic iridium loading of 1.6% was investigated to determine its dimensional stability upon water absorption (100 °C, see Methods). The CCM showed a dimensional change of 1.6% in length and 3.0% in width, which corresponds to an area expansion of 4.6%.
[0054] By using a membrane with high dimensional stability, the corresponding CCM also showed high dimensional stability.
[0055] 0.261mg / cm 2 The swelling behavior of the same CCM with an anodic iridium loading of was also investigated in water at lower temperatures. At room temperature, the area expansion was 3.9%, whereas at a temperature of 80 °C, the area expansion was 4.1%.
[0056] Comparative Example 1: Prior art CCM production and varying anode iridium loading The prior art CCM was prepared in a similar manner to the procedure of Example 1, except that the membrane used was Nafion™ NR212 (Chemours, USA), which has a thickness of about 50 μm and is an established membrane in the PEM-WE publication.
[0057] The linear dimensional change rate of the NR212 membrane when absorbing water (100℃) was 20.0% and 19.7%, respectively. As a result, the area expansion rate was 43.6%.
[0058] The anode and cathode used correspond to those of example 1.
[0059] Similarly, for the five CCMs, the following anode iridium loadings were obtained: 0.155 mg / cm 2 , 0.303 mg / cm 2 , 0.504 mg / cm 2 , 1.068 mg / cm 2 , and 2.102 mg / cm 2 .
[0060] Despite using the same electrodes as in Example 1, slight load non-uniformity during application to the decal substrate resulted in slightly different loads compared to the CCM in Example 1. However, the differences were small enough to allow for informative CCM series comparisons.
[0061] 0.303mg / cm 2 The CCM with NR212 having an anodic iridium loading of 1.0 was additionally investigated to measure its dimensional stability upon absorption of water (100 °C, see Methods). The CCM showed a dimensional change of 15.7% in length and 15.9% in width, which corresponds to an area expansion of 34.1%.
[0062] By using membranes with low dimensional stability, the corresponding CCMs were similarly low in dimensional stability.
[0063] 0.303mg / cm 2The swelling behavior of the same CCM with an anodic iridium loading of was also investigated in water at lower temperatures. At room temperature, the area expansion was 14.4%, whereas at a temperature of 80 °C, the area expansion was 26.6%.
[0064] As already mentioned in the Methods section, the swelling behaviour in water heated to 100 °C at 1013 hPa pressure also correlates with the swelling behaviour at lower temperatures.
[0065] Comparison of output / efficiency in water electrolysis cells - CCM of Example 1 and CCM of Comparative Example 1 The CCMs from Example 1 and Comparative Example 1 were electrochemically characterized in a water electrolysis cell according to the method described above (see section "Power / Efficiency in Water Electrolysis Cell"). The results, i.e., cell voltage at a given current density as a function of anode catalyst loading (anode precious metal loading), are shown in Figures 1 to 4. The data show that at the two temperatures investigated, the anode catalyst loading was 0.6 mg / cm 2 Equivalent to or less than 1A / cm 2 It can be seen that above 1 A / cm, CCMs with high dimensional stability show better efficiency than CCMs with membranes with low dimensional stability. To produce large amounts of hydrogen per unit area and unit time of electrolyzer, the current densities involved in use are higher (>1 A / cm). 2 It is important to mention that
[0066] Further details, advantages and features of the invention will become apparent from the following description of exemplary embodiments with reference to the drawings. [Brief description of the drawings]
[0067] [Figure 1] FIG. 1 shows the cell voltage at a current density of 3.0 A / cm2 as a function of the anode catalyst loading at a cell temperature of 80° C. for Example 1 and Comparative Example 1. [Diagram 2] FIG. 2 shows the cell voltage at a current density of 1.2 A / cm2 as a function of the anode catalyst loading at a cell temperature of 80° C. for Example 1 and Comparative Example 1. [Diagram 3] FIG. 3 shows the cell voltage at a current density of 0.05 A / cm2 as a function of the anode catalyst loading at a cell temperature of 80° C. for Example 1 and Comparative Example 1. [Figure 4] FIG. 4 shows the cell voltage at a current density of 3.0 A / cm2 as a function of the anode catalyst loading at a cell temperature of 65° C. for Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0068] FIG. 1 shows the cell voltages of the water electrolysis cells of Example 1 and Comparative Example 1 at a current density of 3.0 A / cm 2 , for various anode iridium loadings at a cell temperature of 80° C. A comparison of a CCM having a membrane with high dimensional stability and therefore low areal expansion according to the invention (triangles; Example 1) with a CCM having a membrane with low dimensional stability and therefore high areal expansion (circles; Comparative Example 1) shows that 0.6 mg / cm 2 The advantage of using a dimensionally stable membrane is clearly shown below the anode loading, where the improvement in cell voltage is more than 40 mV.
[0069] FIG. 2 shows the current density of 1.2 A / cm for the water electrolysis cells of Example 1 and Comparative Example 1. 2 1 shows the cell voltage for various anode iridium loadings at a cell temperature of 80° C. A comparison of a CCM having a membrane with high dimensional stability and therefore low areal expansion according to the invention (triangles; Example 1) with a CCM having a membrane with low dimensional stability and therefore high areal expansion (circles; Comparative Example 1) shows that 0.6 mg / cm 2 The advantage of using a dimensionally stable membrane at the following anode loadings is clearly shown.
[0070] Figure 3 shows the current density of 0.05 A / cm for various anode iridium loadings. 2 1 shows the cell voltages of the water electrolysis cells of Example 1 and Comparative Example 1 at a cell temperature of 80° C. The power / efficiency in this low current density region is similar over the entire range of anode loadings for the two membrane types. 2 loading and 0.2mg / cm2 The voltage difference for both loadings is in the range of 45 to 50 mV, which corresponds to a slope of 45 to 50 mV / decade, and thus corresponds to the theoretical prediction for an iridium oxide OER catalyst. Although this slope should strictly be calculated based on the resistance-corrected cell voltage, a correction of only a few mV is negligible at such low current densities, and thus ignoring the correction for both loadings does not change the slope and the conclusions that can be drawn from it.
[0071] In addition to the above written description of the present invention, for the sake of supplementary disclosure, explicit reference is made to the schematic representations of the present invention in Figures 1 to 4. Figure 4 shows the cell voltages of the water electrolysis cells of Example 1 and Comparative Example 1 at a current density of 3.0 A / cm 2 , at a cell temperature of 65° C., for various anode iridium loadings. A comparison of a CCM having a membrane with high dimensional stability and therefore low areal expansion according to the invention (triangles; Example 1) with a CCM having a membrane with low dimensional stability and therefore high areal expansion (circles; Comparative Example 1) shows that the anode iridium loading of 0.6 mg / cm 2 The improvement in cell voltage is more than 40 mV, clearly showing the advantage of using a dimensionally stable membrane at below anode loading. [Prior art documents] [Non-patent literature]
[0072] [Non-Patent Document 1] M. Bernt et al., The Electrochemical Society, 165(5)F305-F314(2018)
Claims
1. 1. A water electrolysis cell including a catalyst coated membrane, A proton exchange membrane; an anode applied to the first side of the membrane, the anode comprising at least one precious metal-containing catalyst, the precious metal-containing catalyst having an areal weight of 0.6 mg / cm 2 an anode, a cathode applied to a second side of the membrane; Equipped with the proton exchange membrane includes at least one recombination catalyst that catalyzes the reaction of hydrogen crossing over from the cathode to the anode with oxygen from the anode side; A water electrolysis cell, wherein the catalyst coated membrane has an area expansion of less than 20% after being held in water heated to 100° C. for 2 hours.
2. 2. The water electrolysis cell of claim 1, wherein the catalyst coated membrane has an area expansion rate of less than 15% after being held in water heated to 100° C. for 2 hours.
3. 3. The water electrolysis cell according to claim 1, wherein the catalyst coated membrane has an area expansion rate of less than 10% after being held in water heated to 100°C for 2 hours.
4. The surface weight of the precious metal-containing catalyst based on the precious metal content is 0.4 mg / cm 2 4. The water electrolysis cell according to claim 1 , wherein:
5. The surface weight of the precious metal-containing catalyst based on the precious metal content is 0.35 mg / cm 2 5. The water electrolysis cell according to claim 1 , wherein:
6. The surface weight of the precious metal-containing catalyst based on the precious metal content is 0.02 mg / cm 2 The water electrolysis cell according to claim 1 .
7. The surface weight of the precious metal-containing catalyst based on the precious metal content is 0.05 mg / cm 2 The water electrolysis cell according to claim 1 .
8. 8. The catalyst coated membrane of claim 1, wherein the noble metal is selected from iridium and ruthenium.
9. 9. The water electrolysis cell of claim 1, wherein the precious metal-containing catalyst is selected from iridium oxide, ruthenium oxide, mixtures thereof, and alloys thereof.
10. The water electrolysis cell according to claim 1 , wherein the noble metal-containing catalyst is supported on an inorganic support.
11. 11. The water electrolysis cell according to claim 10, wherein the noble metal-containing catalyst is supported on titanium oxide and / or niobium oxide and / or antimony-doped niobium oxide and / or tin oxide and / or antimony-doped tin oxide.
12. 12. The water electrolysis cell of claim 1, wherein the cathode comprises a platinum-containing and / or palladium-containing cathode catalyst.
13. 13. The water electrolysis cell of claim 12, wherein the platinum-containing and / or palladium-containing cathodic catalyst is present on a carbon-containing support material.
14. 14. The water electrolysis cell according to claim 1, wherein the proton exchange membrane has a layer thickness of 5 to 120 μm.
15. 15. The water electrolysis cell according to claim 1, wherein the proton exchange membrane has a layer thickness of 15 to 90 μm.
16. 16. The water electrolysis cell according to claim 1, wherein the proton exchange membrane has a layer thickness of 35 to 75 μm.
17. 2. The water electrolysis cell of claim 1, wherein the recombination catalyst is platinum particles.
Citation Information
Patent Citations
Dehumidifying film, dehumidifying element using dehumidifying film, and production method of them
JP2017192878A
Polymer electrolyte membrane, membrane electrode assembly, and solid polymer fuel cell
WO2018207325A1